Effect of Different Surface Treatments on the Bond Strength of the Hybrid Ceramic Characterization Layer - Grangeiro, Manassés Tercio Vieira [UNESP]; Rossi, Natalia Rivoli [UNESP]; Barreto, Larissa Araújo Lopes [UNESP]; Bottino, Marco Antonio [UNESP]; Tribst, João Paulo Mendes (My University, 2021)
Purpose: Using the microshear bond strength (pSBS) test, this study investigated the bond strength between a hybrid ceramic and the extrinsic characterization layer after different ceramic surface treatments. Materials and Methods: Hybrid ceramic blocks (Vita Enamic, Vita Zahnfabrik) were sectioned and randomly divided into 4 groups (N = 120) according to the surface treatment and aging (n = 15): P: polishing; E: acid etching with HF; A: aluminum oxide blasting; S: self-etching ceramic primer. The specimens were silanized, then cylinders of light-curing characterization material (Vita Enamic Stain, 1.6 mm diameter x 2 mm height) were fabricated, followed by glazing. The specimens were subsequently immersed in distilled water for 24 h and subjected to the pSBS test using a universal testing machine (load cell 0.5 mm/min, 50 kgf) or tested after thermocycling for 10,000 cycles in water (5°C-55°C). After treatment, the specimen surfaces were analyzed using SEM, with failure types defined as adhesive, predominantly adhesive, or cohesive. The data were analyzed by two-way ANOVA followed by Tukey's test (p < 0.05). Results: The most frequent failure type was predominantly adhesive between ceramic and the characterization layer. There were statistically significant differences between the surface treatments (p < 0.05). Thermocycling did not lead to statistically signifcant different results (p > 0.05). For groups P and A, a sharp decrease in SBS was observed. Conclusion: The absence of surface treatment drastically reduced the microshear bond strength between the ceramic and the characterization layer. Conditioning with 5% hydrofluoric acid for 60 s is the most suitable treatment for adhesion of the characterization layer to hybrid ceramic.
Keywords: bond strength; ceramic; hybrid ceramic